The Effect of Advertising and Trust on Interest in Becoming a Rumah Zakat Donor on Shopee E-Commerce in Bandung City - Fitri, Ajeng Tri Ayunda (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the effect of Shopee e-commerce advertising and trust on interest in becoming a donor who wants Rumah Zakat service products on Shopee e-commerce in Bandung. The research method used in this research is survey research with a descriptive and verification approach. The population in this study is an interest in becoming a donor who wants Rumah Zakat service products at Shopee e-commerce in the city of Bandung. The sampling technique used in this study is non-probability with purposive sampling, with a total sample of 110 respondents. While the analytical method used in this study is multiple linear regression analysis, and the coefficient of determination at a significant level of 5%. This research was assisted by the statistical tool SPSS version 24.0. The results of the study explain that the advertising variable is proven to be able to influence interest in becoming a donor, the better the concept in making advertisements, the more attractive the interest in becoming a donor due to a positive influence. Trust is proven to be able to influence interest in becoming a donor, the more trust in Shopee e-commerce, the more interest in becoming a donor